2007
DOI: 10.1111/j.1540-8159.2007.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

It Is Time to Include P‐Wave Duration

Abstract: There has been sustained interest in the importance of the P-wave duration in predicting a predisposition to atrial arrhythmias. 1-7 Many factors such as left atrial enlargement, left atrial hypertension, and altered conduction may affect P-wave duration. 11 P-wave duration has been shown to be highly correlated with intratrial conduction times. 12 Prolongation of intratrial and interatrial conduction times and the inhomogeneous propagation of sinus impulses are well-known electrophysiologic characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In our survey, the majority (66%) of respondents who performed septal pacing reported a septal lead dislodgement rate of ≤3%. While we accept that these are self-declared figures, the lead dislodgment rates we obtained (Table I) overlap those reported by Burri et al 1 Interestingly, we were unable to demonstrate a statistically significant association between operator volume and frequency of lead displacement, suggesting perhaps, that the learning curve for the procedure may not be very steep. The heterogeneity in current lead placement probably reflects the as-yet undetermined long-term outcomes with RV septal pacing.…”
Section: Right Ventricular Septal Pacing To the Editorsupporting
confidence: 75%
See 2 more Smart Citations
“…In our survey, the majority (66%) of respondents who performed septal pacing reported a septal lead dislodgement rate of ≤3%. While we accept that these are self-declared figures, the lead dislodgment rates we obtained (Table I) overlap those reported by Burri et al 1 Interestingly, we were unable to demonstrate a statistically significant association between operator volume and frequency of lead displacement, suggesting perhaps, that the learning curve for the procedure may not be very steep. The heterogeneity in current lead placement probably reflects the as-yet undetermined long-term outcomes with RV septal pacing.…”
Section: Right Ventricular Septal Pacing To the Editorsupporting
confidence: 75%
“…Over a 5-year period, Burri et al found that septal pacing wires had to be repositioned almost as frequently as RV apical leads. 1 Significantly, their electrode dislodgement rate of 1.3% accords with the national data on lead dislodgment from the UK experience of septal pacing (see below).…”
Section: Right Ventricular Septal Pacing To the Editorsupporting
confidence: 65%
See 1 more Smart Citation
“…29 Our findings and most of published results indicate that it would be of value to the clinician to look at P-wave duration as a potential risk factor to predict clinically significant AF recurrences. 30…”
Section: Previous Studiesmentioning
confidence: 99%
“…The most significant variability over time was reported by the P wave duration. This result agrees with a wide variety of previous works which have also identified this metric as a successful indicator of atrial conduction defects . Nonetheless, the spectral feature P 80 also revealed a highly significant ability to follow successfully P wave morphology progression before the onset of PAF.…”
Section: Discussionmentioning
confidence: 99%